Conocimientos y actitudes sobre la sexualidad en los adolescentes de bachillerato de las instituciones oficiales de la zona urbana del distrito de Riohacha – La Guajira (2020)
The knowledge and attitudes about sexuality are an important factor that must be considered by the adolescents, to avoid negative consequences, like early pregnancy, sexual transmission infections and even abortion. For this, it developed the objective of describe the knowledges and attitudes about sexuality in the adolescents of high school in the Official Educative Institutions of the urban zone of Riohacha district, La Guajira. It was applied the standardized instrument for sex knowledge and attitude SKAT, which addresses to dimensions heterosexuality, abortion, sexual myths and autoeroticism. The results indicate that exist a 58% of the surveyed with a favorable trend about heterosexuality, the 100% showed an acceptance to the abortion; while a 61% showed a trend to believe the sexual myths, and the 100% showed a medium trend to the autoeroticism. Evidenced that the 77% of the surveyed adolescents show a medium level of knowledge about sexuality, while the 23% presents a high level of knowledge, so it is recommended stimulate sexual education workshops to increase the levels of knowledge in matters of sexuality in the adolescent’s field in the schools of the Riohacha district, La Guajira.